Magnetically Separable CuFe2O4 Nanoparticles in PEG: A Recyclable Catalytic System for the Amination of Aryl Iodides - Kumar, A. Suresh; Ramani, T.; Sreedhar, B. (Synlett, 2013)
A recyclable catalytic system comprising magnetically separable CuFe2O4 nanoparticles in a poly(ethylene glycol) medium has been established as an inexpensive, nontoxic, environmentally benign system for the amination of aryl iodides with aqueous ammonia. A wide variety of aryl iodides underwent amination to afford the corresponding aryl amines in moderate to good yields. The catalytic system was recycled five times with consistent activity.
Keywords: amination; aryl iodides; aqueous ammonia; CuFe2O4; aromatic amines